Ankle joint synoviography in rheumatoid arthritis. Issue 6 (December 1977) - Hug, G; Dixon, A S
Abstract : Twenty-six ankles of 23 patients with seropositive or negative arthritis and 24 ankles of 12 cadavers as a control group were studied by contrast synoviography. The main features in the patients were capsule enlargement, hypertrophic synovitis, and connections to tendon sheaths and to the posterior subtalar joint. None of the controls showed capsule distension or irregular outline of the joint cavity, but connections to tendon sheaths and/or to the posterior subtalar joint were present. Other features such as tibiofibular recess, early lymphatic filling, and joint destruction were seen.